Adopting Emerging Technologies for Business Success. (24th December 2020) - Baucherel, Kate
Abstract: Digital strategist Kate Baucherel, author of Blockchain Hurricane: Origins, Applications and Future of Blockchain and Cryptocurrency examines the importance of lifelong learning in harnessing increasingly rapid innovations in tech.